Clinical and morphological parallels in the choice of surgical treatment in patients with chronic critical lower limb ischemia. - Shkuropat, V. M.; Tverdokhlib, I. V.; Drjuk, M. F. (Морфологія / Morphologia / Morfologìâ, 2011)
The purpose of this study was to compare clinical, laboratory and morphological data, obtained from the patients with chronic critical lower limb ischemia, that had direct, indirect or composite revascularization, to compare the dynamics in immediate and distant postoperative periods, depending on patient’s age. Three groups of patients were used in this study: 1) 37 patients with femoral-tibial reconstruction; 2) 57 patients with indirect revascularisation and bone marrow autotransplantation; 3) 50 patients with composite revascularization surgery. The observation was carried out in the near-term postoperative period and within following 2 years. Our results show that proposed method of composite limb revascularization used according to proposed indications provides best normalizing effect. Performing of automyelotransplantation as an independent procedure of indirect revascularization or a component of composite revascularization leads to substantial increase of the concentration of VEGF factor in blood at 6 and 12 months following surgery, revealed in patients of all the age groups except those of an old age. The intensity of VEGF synthesis stimulation is related essentially to the properties of the bone marrow aspirate. The stimulation of synthetic activity takes place to the utmost when automyelotransplantation is performed on the patients of young and mature age, to a lesser degree when patients are of middle age. In the patients of 75 years and older the effect of using of bone marrow aspirate during the direct or composite revascularization wasn’t revealed. Proposed method for assessing the adequacy of the fibular artery allows to optimize the choice of method of revascularization with the use of limb reconstructive surgery on the arteries independently, or in combination with indirect revascularization using autologous bone marrow aspirate.